DEVELOPMENT OF STEM-BASED E-LKPD IN THE SUBJECT OF AQIDAH AND AKHLAK TO IMPROVE STUDENT LEARNING OUTCOMES - Rabba Yenni Pardosi; Munawir Pasaribu; Robie Fanreza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research aims to develop and test the effectiveness of STEM-based E-LKPD on Commendable Morals material for grade XI students of MAN Dairi. The research uses the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of two classes: class XI Science 2 as an experimental class and class XI Science 3 as a control class. Data was collected through tests and questionnaires, then analyzed using validity, reliability, and Independent-Samples T-Test tests with the help of SPSS 26. The results showed that STEM-based E-LKPD obtained an average validity value of 94.9% with the "very feasible" category and practicality of 94% with the "very good" category. The effectiveness test showed an increase in pretest and posttest scores, namely in the medium category, in addition there was a significant difference between the experimental and control classes with a value of Sig. (2-tailed) = 0.010 < 0.05. The results of the effect size test also showed that 10.8% had an effect on the effectiveness of the use of E-LKPD in learning. This proves that the use of STEM-based E-LKPD is effective in improving student learning outcomes. Advanced research can integrate other 21st-century capability indicators such as creativity, collaboration, and communication to strengthen students' holistic competencies.